Pengaruh Inflation, Interest Rate, dan Exchange Rate terhadap IHSG di Bursa Efek Indonesia pada Tahun 2011-2021 - Hesniati Hesniati; Andreas Yoshiro Ogawa; Arvin Clarence; Chris Topher; Jerly Engelina (Studi Ilmu Manajemen dan Organisasi, 2022)
Purpose: The purpose of this study is to develop a model and research the influence of macroeconomics ranging from inflation, exchange rates and interest rates towards the growth of the IHSG Research methodology: A total of 132 sample data were used and were collected from 2011 to 2021. Quantitative research methods were used in conjunction with the use of SPSS analysis tool. Results: The research shows that macroeconomic does indeed have an effect on the IHSG. Inflation didn’t have a significant effect on IHSG, Interest rates was found to have a significant negative effect on the IHSG, The exchange rate was found to have a significant effect on IHSG. Limitations: The sample data was collected from numerous statistics website, but there appears to be slight numerical inconsistencies between the data presented. As such, the sample data used in the research were collected from only the most credible sources. Contribution: Can be a reference for future research regarding the same subjects, variables and phenomenon.